The Management of Ecclesiastical Incomes in the Kingdom of Granada: The Case of the Parishes of the Alpujarra, 1501-1526 (Edad Media. Revista de Historia, 2020)
In this article, there will be an analysis of administrative and fiscal structure of the Alpujarra’s churches, in the kingdom of Granada, after the general conversión of its muslim inhabitants to Christianity. The management of the two main sources of income, consisting in tithes and bienes habices, would be at first under the control of the Royal Treasury. This changed in the first decade of 1500s, when the Church got its administration. This article studies how this change happened, the levels of both revenues and how the money was managed by the parishes
Keywords: Fiscality; Kingdom of Granada; Tithes; Bienes Habices; Parishes